Pancasila Corner as Reinforcement of Santri’s National Insight Values at Darul Abror Islamic Boarding School - Chamadi, Muhamad Riza; Jamaluddin, Dindin; Az Zafi, Ashif; Partono, Partono; Fuadi, Salis Irvan (ADDIN, 2024)
Darul Abror Islamic Boarding School in Purwokerto is one of the Islamic boarding schools that strive for the national spirit of the students through a national space called Pancasila Corner. This study aims to describe the form of Pancasila Corner activities at Darul Abror Islamic Boarding School and the students’ national motivations through Pancasila Corner. This study uses a qualitative descriptive method by analyzing data from interviews with students and boarding school administrators, field observations, and documentation. The results of this study are: The Pancasila Corner is a scientific forum for discussing Santri’s nationality that provides national literacy. The available national literacy includes historical, political, legal and human rights literacy and contemporary national discourse with academics as facilitators. Santri gets the strengthening of national values in the form of righteousness to God Almighty, the value of tolerance, the value of love for the homeland, the value of cooperation and democratic values.